2016
DOI: 10.7243/2056-3779-3-1
|View full text |Cite
|
Sign up to set email alerts
|

Health and environmental impacts of pesticides: A responsibility principle and two novel systems for hazard classification and external cost determination

Abstract: Environmental policies built on the principles of 'Extended Producer Responsibility' (EPR) have spread to cover multiple categories of products and their containers or packages. Although pesticides are genuinely hazardous to human health and the environment, their negative impacts/externalities have not been targeted by these policies. In this manuscript, the author proposes an overarching 'toxi-economic' principle called the 'Extended Pesticide Producer and User Responsibility' (EPPUR) that justifiably assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
(24 reference statements)
0
8
0
5
Order By: Relevance
“…All of these factors also pose dangers to human beings. Acute and chronic human illnesses are rapidly increasing due to polluted water, air and food as a result of biomagnification of the toxic compounds (Tunaz and Uygun 2004;Brittain et al 2010;Damalas and Eleftherohorinos 2011;Zacharia 2011;Gill and Garg 2014;Ibrahim 2016;Mahmood et al 2016). Considering the various harmful effects of chemical pesticides, appropriate alternative strategies must be developed and explored.…”
Section: Introductionmentioning
confidence: 99%
“…All of these factors also pose dangers to human beings. Acute and chronic human illnesses are rapidly increasing due to polluted water, air and food as a result of biomagnification of the toxic compounds (Tunaz and Uygun 2004;Brittain et al 2010;Damalas and Eleftherohorinos 2011;Zacharia 2011;Gill and Garg 2014;Ibrahim 2016;Mahmood et al 2016). Considering the various harmful effects of chemical pesticides, appropriate alternative strategies must be developed and explored.…”
Section: Introductionmentioning
confidence: 99%
“…and Fusarium solani 4 . The growing global concern about the damages caused by the excessive use of synthetic pesticides in human health, the environment, biodiversity and food security, has led to a general rejection of chemical control in agricultural production 5 . The Food and Agriculture Organization of the United Nations 6 reported that in 2013 global agricultural production of 23.34 trillion tons was obtained; For which 1.29 million tons of pesticides (insecticides, herbicides, fungicides and bactericides) were applied.…”
Section: Introductionmentioning
confidence: 99%
“…La creciente preocupación mundial, por los daños que el empleo excesivo de plaguicidas sintéticos está ocasionando en la salud humana, el medio ambiente, la biodiversidad y la seguridad alimentaria, ha provocado un rechazo generalizado hacia el control químico de plagas en la producción agrícola (Sarwar, 2015;Ibrahim, 2016). Sin embargo, se estima que la restricción de la utilización de dichos agroquímicos tendría como consecuencia bajos rendimientos de los cultivos, encarecimiento y deficiencias en el suministro de alimentos para una población que va en aumento (Storck y col., 2017).…”
Section: Introductionunclassified